Different mechanisms and electrocatalytic activities of Ce ion or CeO2 modified Ti/Sb–SnO2 electrodes fabricated by one-step pulse electro-codeposition1. Issue 25 (21st March 2015) - Duan, Tigang; Chen, Ye; Wen, Qing; Duan, Ying
<x xml:space="preserve">Abstract</x> Nano-CeO2 doping mitigates the surface antimony enrichment and promotes the complete oxidation of antimony, while cerium ion doping aggravates these things.